Factors Related to Children Under Two Consumption Pattern in Locus Stunting Area - Magdalena Octavianus; Erny Erawati Pua Upa; Marselinus Laga Nur (Universitas Nusa Cendana, 2020)
Age 0-24 months (baduta) is a period of rapid growth and development, called a golden and critical period. Baduta nutritional health condition depends on the level of consumption, determined by the food quality. Nutritional quality indicates the presence of all nutrients needed by the body and emphasizes food diversity. This study aimed to determine the factors associated with the consumption pattern of baduta in the stunting locus area. This type of research is quantitative research with an observational approach using the Cross-Sectional Study design. This research was conducted in 10 villages in the stunting locus region of TTU with a sample of 178 baduta determined using the total sampling method. Analysis of the data used univariate and bivariate analysis with Chi-Square statistical tests. The study results indicated that factors related to the consumption pattern of baduta were family income (ρ= 0,037) and the number of family members (ρ= 0,033), while the unrelated factor was maternal education. This study suggests improving maternal education